Estandarización en la Selección de los Hidrociclones utilizados en el Proceso de Producción Mediante la Simulación Computacional (2019)
In this project we present the most used methods in the separation of production fluids focused mainly on the treatment of production water, and the generalities of the hydrocyclones used in the oil industry are presented, as are the de-sander in the drilling phase and de-oilers in the production phase; making a detailed description in the de-oiling type hydrocyclones, where the design parameters are defined in a general way and in detail the operation parameters and the effect they have on the separation efficiency. The ASAP company uses deoiling hydrocyclones as a wastewater treatment method, but currently they do not have the most effective operating ranges for field implementation, and that is why their installation is empirical and based on the trial and error method. . In order to find these operating ranges, computational simulations are performed, which show the behavior of the fluids inside the hydrocyclone and allow its analysis. In addition, the results generated will be gathered and exposed through a matrix of results in order to technify the installation of hydrocyclones. Finally, a financial evaluation is carried out comparing the selection method used by the company and the one proposed by the project. To carry out the evaluation, the equivalent uniform annual cost (CAUE) is used as a financial indicator, which shows a 5-year projection of the savings generated by the company when implementing the project.